Impact of Transition Metal Ions on the Oxidation of Perfumery Alcohols - Prabhu, Damodar V.; Parbat , Harichandra A.; Rana , Chetana N.; Gupta, Himanshu (Current Topics on Chemistry and Biochemistry Vol. 4, 2022)
The aim of this investigation is to study the catalytic impact of transition metal ions on the oxidation of a variety of perfumery and fragrance alcohols by Ce (IV) in an acidic medium using kinetic methods. The quantitative aspects of the oxidation of alcohols to aldehydes/ketones have been extensively studied and reported in literature but there are few reports of the kinetic and thermodynamic studies of the oxidation of alcohols.Environmentally hazardous metal ions, Cr (VI), Os (VIII) and Ru in different oxidation states have been routinely used to catalyze the oxidation of alcohols.We have investigated the oxidation of perfumery and fragrance alcohols using Ce(IV) as oxidant in acidic medium.As a green initiative ,less harmful and inexpensive transition metal ions have been effectively used to catalyze the oxidation of 1) primary acyclic alcohols,Geraniol,Nerol and Citronellol, 2)secondary cyclic alcohols,Borneol and Isoborneol and 3)primary unsaturated alcohol,Cinnamyl alcohol. Using kinetic methods, the oxidation rates of alcohols were determined under first order kinetic conditions with respect to the inorganic oxidant.For each alcohol,the oxidation rate increased with [alc.] but decreased with Ce(IV) concentration.From the variation of oxidation rate with temperature,the energy of activation and thermodynamic activation parameters were evaluated and interpreted in terms of the molecular dynamics of the oxidation process. The sequence of catalytic efficiencies of the transition metal ions were determined for each perfumery alcohol and compared with the expected sequence based on Irwing-Williams stability orderof the metal complexes formed as unstable intermediates during the oxidation reaction.The oxidation rates of alcohols increase with transition metal on concentration.Suitable reaction mechanisms have been suggested for the oxidation of the perfumery alcohols in the presence and absence of transition metal ion catalysts.